Предмет: Алгебра,
автор: SneSne
Решить:
12x-20x^3
(2a-3c)(a+2c)
(y-1)(y^2y+-4)
(3x^3-6x^2)÷9x
2a(a+b-c)-2ab(a-b-c)+2c(a-b+c)
Сократить:
-0,3a(4a^2-3)(2a^2+5)
^2 - в квадрате (2 степень)
^3 - в кубе (3 степень)
Ответы
Автор ответа:
0
-0,3a(4a^2-3)(2a^2+5)=(-1,2a^3+0,9а)(2a^2+5)=-2,4a^5-6a^3+1,8a^3+4,5a=4,5а-2,4a^5-4,2a^3=а(4,5-2,4a^4-4,2a^2)
2a(a+b-c)-2ab(a-b-c)+2c(a-b+c)=2a^2+2ab-2ac-2a^2b+2ab^2+2abc+2ca-2cb+2c^2=
2a^2+2ab-2a^2b+2ab^2+2abc-2cb+2c^2=2a(a+b-ab+b^2)-2c(ab-b+c)
2a(a+b-c)-2ab(a-b-c)+2c(a-b+c)=2a^2+2ab-2ac-2a^2b+2ab^2+2abc+2ca-2cb+2c^2=
2a^2+2ab-2a^2b+2ab^2+2abc-2cb+2c^2=2a(a+b-ab+b^2)-2c(ab-b+c)
Похожие вопросы
Предмет: Физика,
автор: ruqiyaakmalova10
Предмет: Українська мова,
автор: yogkxkglhyhfxnkffkkf
Предмет: Геометрия,
автор: Neisvestniio
Предмет: Математика,
автор: Во0олег0Во